Phytochemical Investigation of n-Hexane Extract of Leaves of Cleome gynandra - RANJITHA, J.; BAKIYALAKSHMI, K.; ANAND, M.; SUDHA, P.N. (Asian Journal of Chemistry, 2010)
Dried and powdered leaves of Cleome gynandra were extracted using n-hexane solvent. From this extract, four individual components were identified using GC-Mass technique. The identified components were isolated in their pure form using column chromatography. The identity of these 4 isolated components was confirmed by spectral interpretation. These isolated components showed inhibitory activity against various bacteria and fungi.